Quality of dietary macronutrients is associated with glycemic outcomes in adults with cystic fibrosis - Daley, Tanicia C.; Cousineau, Benjamin A.; Nesbeth, Paula-Dene C.; Ivie, Elizabeth A.; Bellissimo, Moriah P.; Easley, Kirk A.; Vellanki, Priyathama; Vos, Miriam B.; Hunt, William R.; Stecenko, Arlene A.; Ziegler, Thomas R.; Alvarez, Jessica A. (Frontiers in Nutrition, 2023)
ABSTRACT/SUMMARY Objective: Poor diet quality contributes to metabolic dysfunction. This study aimed to gain a greater understanding of the relationship between dietary macronutrient quality and glucose homeostasis in adults with cystic fibrosis (CF). Design: This was a cross-sectional study of N=27 adults with CF with glucose tolerance ranging from normal (n=9) to prediabetes (n=6) to being classified as having cystic fibrosis- related diabetes (CFRD, n=12). Fasted blood was collected for analysis of glucose, insulin, and C-peptide. Insulin resistance was assessed by Homeostatic Model Assessment for Insulin Resistance (HOMA2-IR). Subjects without known CFRD also underwent a 2-hr oral glucose tolerance test. Three-day food records were used to assess macronutrient sources. Dietary variables were adjusted for energy intake. Statistical analyses included ANOVA, Spearman correlations, and multiple linear regression. Results: Individuals with CFRD consumed less total fat and monounsaturated fatty acids (MUFA) compared to those with normal glucose tolerance (p<0.05). In Spearman correlation analyses, dietary glycemic load was inversely associated with C-peptide (rho= –0.28, p=0.05). Total dietary fat, MUFA, and polyunsaturated fatty acids (PUFA) were positively associated with C-peptide (rho=0.39-0.41, all p<0.05). Plant protein intake was inversely related to HOMA2-IR (rho= –0.28, p=0.048). Associations remained significant after adjustment for age and sex. Discussion: Improvements in diet quality are needed in people with CF. This study suggests that higher unsaturated dietary fat, higher plant protein, and higher carbohydrate quality were associated with better glucose tolerance indicators in adults with CF. Larger, prospective studies in individuals with CF are needed to determine the impact of diet quality on the development of CFRD.